Patient portal utilization: before and after stage 2 electronic health record meaningful use. (4th April 2019) - Turner, Kea; Hong, Young-Rock; Yadav, Sandhya; Huo, Jinhai; Mainous, Arch G
Abstract: Objective: Patient portal functionalities, such as patient–physician e-communication, can benefit patients by improving clinical outcomes. Utilization has historically been low but may have increased in recent years due to the implementation of Stage 2 Meaningful Use for electronic health records. This study has 2 objectives: 1) to compare patient portal utilization rates before Stage 2 (2011–2013) and after Stage 2 (2014–2017), and 2) to examine whether disparities in patient portal utilization attenuate after Stage 2. Materials and Methods: We conducted an observational study using a pooled cross-sectional analysis of 2011–2017 National Health Interview Survey data ( n  = 254 183). Results: The mean percent use of patient portals significantly increased from the pre-Stage 2 to the post-Stage 2 period (6.9%, 95% CI, 6.2–7.5; P  < .001). Non-Hispanic Black individuals (OR 0.81, 95% CI, 0.76–0.86; P  < .0001) and Hispanic individuals (OR 0.79, 95% CI, 0.74–0.84; P  < .0001) have lower odds of using patient portals compared to non-Hispanic White individuals. Although we found independent effects of race/ethnicity, we did not find a statistically significant interaction between race/ethnicity and time. We found a similar level of increase in patient portal utilization from the pre- to postperiod across racial and ethnic groups. Discussion: Health care policies such as Stage 2 Meaningful Use are likely contributing to increased patient portal utilization across all patients and helping to attenuate disparities in utilization between subgroups of patients. Conclusion: Further research is needed to explore which patient portal functionalities are perceived as most beneficial to patients and whether patients have access to those functionalities.